Динамическая модель электромеханических процессов в электромагнитном вибраторе с реактивными массами - Черно, А.А.; Гуров, А.П.; Минчула, А.С.; Безверхний, Д.Л. (Електротехніка і електромеханіка, 2011)
A dynamic model of electromechanical processes in an electromagnetic vibrator with two symmetrically located reactive masses has been worked out. The model takes into account rotary motion of the electromagnet armatures, local saturation of the steel, and leakage fluxes. The model introduced can be used for computation of electromagnetic vibrators dynamics with the purpose of a rational choice of their parameters at designing and also for analysis and synthesis of electromagnetic vibrator automatic control systems.